Increasing Health Insurance Enrollment in Low- and Middle-Income Countries: What Works, What Does Not, and Research Gaps: A Scoping Review. (May 2022) - James, Nigel; Acharya, Yubraj
Health insurance programs have the potential to shield individuals in low- and middle-income countries from catastrophic health expenses and reduce their vulnerability to poverty. However, the uptake of insurance programs remains low in these countries. We reviewed existing evidence from experimental studies on approaches that researchers have tested in order to raise the uptake. In the 12 studies we synthesized, educational programs and subsidies were the dominant interventions. Consistent with findings from previous studies on other health products, subsidies were effective in raising the uptake of insurance programs in many contexts. Conversely, education interventions—in their current forms—were largely ineffective, although they bolstered the effect of subsidies. Other strategies, such as the use of microfinance institutions and social networks for outreach and enrollment, showed mixed results. Additional research is needed on effective approaches to raise the uptake of insurance programs, including tools from behavioral economics that have shown promise in other areas of health behavior.